Prurigo pigmentosa - (:unkn) unknown (WILEY, 1999)
Case I A 28-year-old woman with skin type 2 was first seen in May 1997 with a 10-year history of a recurrent pruritic eruption in the intermammary area. Her medical history was not significant regarding a systemic disease or a triggering factor that could have been related to her eruption. Results of laboratory investigations, including peripheral brood cell counts, liver and renal function tests, blood glucose levels, and urinalysis, were within normal limits. Physical examination revealed erythematous papules and reticulated hyperpigmentation in the intermammary area. Histopathologic examination from an erythematous papule showed parakeratosis, mild acanthosis, spongiosis, dyskeratotic keratinocytes, and focal Vacuolar degeneration of basal keratinocytes within the epidermis; and perivascular lymphocytic infiltrate and pigment incontinence within the upper dermis (Fig. 1), Following an initial treatment with topical corticosteroid for 2 weeks with a partial response, doxycycline was started in 200 mg daily doses for 3 weeks. The eruption resolved leaving marked residual hyperpigmentation within 3 weeks. No recurrence has been observed over the past 6 months. Case 2 A 23-year-old woman with skin type 3 presented in June 1997 with a 2-month history of a recurrent pruritic eruption on her chest. She denied any provoking factor that could have been responsible for her eruption. Her examination revealed erythematous papules and reticulated hyperpigmentation localized to the inframammary area (Fig. 2). Skin biopsy showed focal parakeratosis, minimal acanthosis, spongiosis, and a lymphocytic infiltrate around the blood Vessels of the upper dermis. The lesions resolved spontaneously leaving residual reticulated hyperpigmentation within 2 weeks. The following course of her lesions is not known as she was lost to follow-up.
Keywords: ERUPTION; KETOSIS; ICAM-1